Glioblastoma Multiforme versus Solitary Supratentorial Brain Metastasis: Differentiation Based on Morphology and Magnetic Resonance Signal Characteristics - Maurer, M. H.; Synowitz, M.; Badakshi, H.; Lohkamp, L. N.; Wüstefeld, J.; Schäfer, M.-L.; Wiener, E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To evaluate the diagnostic potential of a multi-factor analysis of morphometric parameters and magnetic resonance (MR) signal characteristics of a mass and peritumoral area to distinguish solitary supratentorial metastasis from glioblastoma multiforme (GBM). Materials and Methods: MR examinations of 51 patients with histologically proven GBM and 44 with a single supratentorial metastasis were evaluated. A large variety of morphologic criteria and MR signal characteristics in different sequences were analyzed. The data were subjected to logistic regression to investigate their ability to discriminate between GBM and cerebral metastasis. Receiver-operating characteristic (ROC) analysis was used to select an optimal cut-off point for prediction and to assess the predictive value in terms of sensitivity, specificity, and accuracy of the final model. Results: The logistic regression analysis revealed that the ratio of the maximum diameter of the peritumoral area measured on T2-weighted images (d T2) to the maximum diameter of the enhancing mass area (d T1, post-contrast) is the only useful criterion to distinguish single supratentorial brain metastasis from GBM with a lower ratio favoring GBM (accuracy 68 %, sensitivity 84 % and specificity 45 %). The cut-off point for the ratio d T2/d T1 post-contrast was calculated as 2.35. Conclusion: Measurement of maximum diameters of the peritumoral area in relation to the enhancing mass can be evaluated easily in the clinical routine to discriminate GBM from solitary supratentorial metastasis with an accuracy comparable to that of advanced MRI techniques.
Keywords: glioblastoma multiforme; brain metastases; multi-factor analysis; morphologic criteria; magnetic resonance imaging